Analisis Pelembagaan Partisipasi Politik Akar Rumput melalui Gerakan Kelompok Tani di Kabupaten Bireuen, Provinsi Aceh - Mulyadi, Mulyadi; bin Abubakar, Muhammad; Abdullah, Taufik; Hidayat, Bimby (Universitas Indo Global Mandiri, 2024)
Increasing political participation is certainly not an easy job, there needs to be support from several parties or groups. One group that is considered capable of inviting people to increase political participation is farmer groups. Especially for people who live in rural areas. One of the villages that has a farmer group is Gampong Blang Cut, Peusangan District in Bireuen Regency. The purpose of the research is to find out the role of the farmer group in increasing community political participation and to find out the obstacles faced by farmer groups in increasing community political participation. The research method uses qualitative techniques. The results of this study indicate that; the level of participation of farmer groups tends to be low. Constraining factors such as gaps in the political capacity of farmer groups, fragmentation and limited resources, apathy and dependence on the government are often the main causes of the low political participation of farmer groups. This situation ultimately weakens the capacity of farmer groups to develop and fight for a political agenda that truly reflects their needs and aspirations. Therefore, systematic efforts are needed to restructure farmer group organizations to be more oriented towards political participation such as; (1) Recognition of Customary Values; (2) Community involvement in the decision-making process of village development; (3) Strengthening the partnership network of grassroots institutions; (4) Strengthening discussion and dialogue forums.